The Role of Public Health Education in Antimicrobial Stewardship: Collaboration Between Nursing, Pharmacy Technicians, and Laboratory Sciences - Freah Abdullah Ali Alamshani8, Maryam Khalil Abdu Almaqadi9, May Ali Mohammed Alkudayisi10, Fatimah Abdullah Ali Alamshani11, Abdulaziz Hassan Abdu Alzubidi12 sharifa sulaiman mousa mulayhi13, Yahya Hussain Ali Halawi1, Laylah Atiah Atiah Almaqadi2, Shuhrrah Atiah Almalki3, Halimah Mohammed Ali Almaqadi4, Hind Omar Noori Alsayed5, Kamlah Ali Mohammad Alkudesi6, Saeed Ali Ahmed Alghubayshi7 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Antimicrobial resistance (AMR) is a serious global health threat, and antimicrobial stewardship (AMS) programs are crucial for promoting the judicious use of antimicrobials. This paper explores the role of public health education in supporting AMS initiatives and emphasizes the collaborative efforts of nursing, pharmacy technicians, and laboratory scientists. Through public health education, healthcare professionals gain the knowledge and skills necessary for patient-centered care, including monitoring antimicrobial use and providing patient counseling. Collaboration among nurses, pharmacy technicians, and laboratory scientists enhances evidence-based decisions and optimizes patient outcomes. Despite challenges such as professional differences and communication barriers, opportunities for improvement include joint training sessions and leveraging health informatics tools. Promoting integrated teamwork can maximize the impact of AMS and address the global challenge of AMR.